European parents' attitudes towards public childcare provision: the role of current provisions, interests and ideologies. Issue 1 (1st January 2017) - Chung, Heejung; Meuleman, Bart
ABSTRACT: Despite the large volume of literature on childcare provision across countries, individuals' attitudes and preferences concerning the role of government in the provision of childcare remain largely unexplored. This study examines how current policy provision structures, measured through objective and subjective indicators, both at the individual and national levels, influence the degree to which parents in European countries support public provision of childcare. The relative importance of current provision structures is then compared with other welfare attitude determinants; that is, self-interest and political attitudes. This is done using data from 22 European countries in 2008/2009 and a multilevel modelling technique. Results show that in general parents across Europe are largely supportive of public childcare provision. Furthermore, current provision structures, and people's assessment of it, are consistently related to parents' support for public childcare. Current provisions are salient factor explaining variance in childcare support (both at the individual and national levels) over and beyond the most commonly used frameworks, namely self-interest and ideologies. The results of this study provide evidence for a vicious and virtuous cycle in the relationship between policy provision and support, where investment in policies may drive up support while rolling back of policies may further decrease support.